2016
DOI: 10.1002/cbic.201600179
|View full text |Cite
|
Sign up to set email alerts
|

A Thioether‐Stabilized d‐Proline–l‐Proline‐Induced β‐Hairpin Peptide of Defensin Segment Increases Its Anti‐Candida albicans Ability

Abstract: We report a β-hairpin dual stabilizing strategy: a d-proline-l-proline (d-Pro-l-Pro) dipeptide as the nucleating turn, and a thioether tether as a side-chain linkage at a precisely designed position to stabilize the β-hairpin. This method was used to modify the C-terminal β-hairpin moiety of the plant defensin, pv-defensin, in order to obtain a stabilized peptide with enhanced anti-Candida albicans activity (MIC 84-3.0 μm), high serum stability (50 % remaining after 48 h) and low hemolysis (<10 % at 152 μm). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…To evaluate whether introducing an extra aromatic residue would increase the overall hydrophobicity and the antimicrobial activity without increasing the toxicity, the analogue [L5W]­cGm, in which Leu5 was replaced with Trp, was designed. Previous studies have shown that the motif d -Pro– l -Pro adopts a rigid turn structure, increasing the β-hairpin stability and the activity against tested yeast . To examine whether this strategy would improve the antimicrobial activity of cGm, we have designed the analogue [ D P L P]­cGm, in which the motif d -Pro– l -Pro was added in a turn.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate whether introducing an extra aromatic residue would increase the overall hydrophobicity and the antimicrobial activity without increasing the toxicity, the analogue [L5W]­cGm, in which Leu5 was replaced with Trp, was designed. Previous studies have shown that the motif d -Pro– l -Pro adopts a rigid turn structure, increasing the β-hairpin stability and the activity against tested yeast . To examine whether this strategy would improve the antimicrobial activity of cGm, we have designed the analogue [ D P L P]­cGm, in which the motif d -Pro– l -Pro was added in a turn.…”
Section: Resultsmentioning
confidence: 99%
“…Biomedical implants and devices, an essential part of the medical treatments for improving therapeutic efficiency, have suffered from bacterial infections that hamper patients’ recovery and even threaten patients’ lives. Although antibiotics are widely used for systematic and local administration to treat infections, it has brought serious problems of antibiotic resistance. Besides small molecule antibiotics, alternative strategies have been explored to inhibit or kill bacteria using polymers that have multiple amine groups or generate reactive oxygen species. Despite antibacterial performance, it is always a consideration to optimize for low cytotoxicity on mammalian cells and sustained activities over time for antibacterial agents. Host defense peptides (HDPs) have been actively studied in recent years because HDPs can have broad-spectrum antibacterial activities and low susceptibility to antimicrobial resistance. Although the low stability, generally moderate activity, and high price of HDPs hamper their application, HDPs are promising models in designing novel antimicrobial agents to fight with drug-resistant microbial infections and antimicrobial resistance. Synthetic β-peptide polymers, also called nylon-3 polymers that are much more stable and much less expensive than HDPs, have proven to be synthetic mimics of HDPs and have broad-spectrum and potent antimicrobial activities in solution. Nevertheless, it is highly desired to prevent implantation-related infections rather than perform antimicrobial treatment after infections happen.…”
Section: Introductionmentioning
confidence: 99%
“…BMP2-Derived/Mimetic Peptides BMP-2, which is a member of the TGF-β super-family, is one of the main chondrogenic growth factors that induce in vitro chondrogenic differentiation and cartilage regeneration in vivo. Human MSCs (hMSCs) cultured with ≥100 µg/mL of the BMP peptide (KIP-KASSVPTELSAISTLYL) resulted in glycosaminoglycan (GAGs) production and increased levels of collagen production and matrix accumulation without extensive upregulation of hypertrophic markers [63,64,[150][151][152]. The injection of BMP-2 mimetic CK2.1 peptide into a mouse's tail vein enhanced chondrogenesis and articular cartilage formation without any effects on osteogenesis or BMD [65].…”
Section: Tgf-β Mimetic Peptidesmentioning
confidence: 99%